(untitled) (Global Journal of Science Frontier Research, 2014)
Morphometric studies aimed at identifying some existing variations among different samples of Callosobruchus subinnotatus (Pic) collected from three locations each of five Northwestern States (Kaduna, Zamfara, Kebbi, Kano and Katsina) in Nigeria was evaluated. Thirteen diagnostic features were used in which measurements were carried out on ten characters using handheld digitalized Miscope microscope (40-140x magnification) while three ratios were used as explanatory variables. Data obtained were analyzed using the parametric statistical tools of mean, standard deviation and standard error. The distribution and relationships among samples studied were expressed using two step cluster analysis, results of which were drawn into cluster distributions, centroids of means of morphoclusters and the simultaneous confidence intervals (95%) used to determining the level of significance among measured variables of the samples. The result gave two morphoclusters revealing the existence of two possible races of C. subinnotatus in Northwestern Nigeria. Race 2 constituted the highest percentage distribution across the States with 53.3% against race 1 with 46.7%. Race 2 were relatively bigger in size than race 1.